Behavior of Young Music Consumers Towards Music Competitions and Reality Shows: A Case of Pepsi Battle of The Bands (Journal of Social Sciences Review, 2025)
This research analyzes the attitudes and tendencies of young music consumers towards music competitions and reality shows, particularly Pepsi Battle of the Bands (BOTB), a known reality show in Pakistan owned by PepsiCo. The applied quantitative approach employs a One-group Pretest-posttest research design for an evaluation of a cohort of Bachelor of Science Students from a randomly selected sample of thirty-two students, with gender-balanced factors in mind. The essence of this design is that it gives a chance to measure the changes in beliefs or feelings before and after the exposure to the intervening factors, in this specific case - the edited showreel with scenes from the earlier season of BOTB. Rigorous statistical analysis is the procedure to fetch results, retrieve the data, treat it with paired t-tests, and then compare the means with the help of the SPSS software. The analysis shows a significant difference between the age and the pretest scores, which statistical data confirms, so a multitude of factors are the cause of their feeling. Despite the difference in the range of age, the average pretest scores of various age levels are similar to each other, implying a consistent attitude on the similar variables expressed. The p-value (
Keywords: Pepsi Battle of the Bands; Pakistan; Music Reality Show; Music Consumers; One-group Pretest-Posttest